Physical chemistry - Levine, Ira N., 1937- (McGraw-Hill, 2009)
"Ira N. Levine's sixth edition of Physical Chemistry provides students with an in-depth fundamental treatment of physical chemistry. At the same time, the treatment is made easy to follow by giving full step-by-step derivations, clear explanations and by avoiding advanced mathematics unfamiliar to students. Necessary math and physics have thorough review sections. Worked examples are followed by a practice."--Books.google.